Pengaruh Digital Payment Terhadap Minat Masyarakat Dalam Membayar Zakat - Ceriah Rukmana; Lya Reinita; Nikmah Toyiba; Fajri Hidayat; Maya Panorama (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
In this modern era, technology is developing very rapidly. Technological developments are used in various fields of life. Technology has also changed the model of financial transactions that used to be done conventionally, now can be done digitally. Not only the conventional economic sector feels the impact of this technological development, Islamic economics also feels the impact. One example of a field that takes advantage of technological developments is the zakat payment mechanism. Zakat can now be done digitally, this certainly makes it easier for humans, both zakat payers and zakat recipients. However, there are also many people who have not fully implemented technological advances in their lives for several reasons. This research uses Internet searching method. Keywords: Digital Zakat, Online Payment System, Transaksi Digital, Zakat payment, Zakat Infaq Sadaqah.